Effect of Potassium Humate on Soybean Germination Traits Under Salinity Stress Conditions - Öner Canavar; Hatice Kübra Gören; Seçil Küçük Kaya; Feride Öncan Sümer (Turkish Journal of Agriculture: Food Science and Technology, 2023)
This study investigated the effects of salinity and K-humate concentrations on soybean germination. The findings contribute to our knowledge of soybean germination under salt stress and the potential use of potassium humate. The experiment was conducted in the laboratory of the Department of Field Crops at Adnan Menderes University, Turkey. Seeds were surface-sterilized and placed on filter paper in Petri dishes. Different concentrations of water (control), NaCl solution (3 dS m-1), and K-humate solution were added. The experiment followed a factorial design with two factors and four replications. K-humate had a positive impact on germination rate. Significant differences were observed among control, salinity, and salinity * K-humate applications. Salinity reduced germination percentage. K-humate mitigated the negative effects of salinity, improving germination. These findings suggest the potential use of K-humate to enhance seedling establishment and overall plant productivity in salinity-affected environments.